Assessment of Anteroposterior Skeletal Relationship Using Different Cephalometric Analysis - Marwa Ahmed Jumaa; Sara M. Al-Mashhadany (Karbala Journal of Medicine, 2025)
In orthodontic diagnosis and treatment planning, precise anteroposterior measurements of jaw relationships are essential. For efficient diagnosis and treatment planning, the sagittal mismatch between the maxilla and mandible is assessed using a variety of angular and linear measurements, especially in orthognathic surgical cases. Cephalometric diagnosis is a crucial part of orthodontic care. This review aimed to identify and summarize the different methods of cephalometric analysis to evaluate anteroposterior skeletal relation.